World Bank East Asia and Pacific Economic Update 2011, Volume 1 : Securing the Present, Shaping the Future - World Bank (Washington, DC, 2013)
Real Gross Domestic Product (GDP) growth in East Asia has been moderating after a sharp rebound from the global crisis. The slowdown in growth since mid-2010, even though smaller than earlier projected, has occurred despite a stronger-than-expected recovery in high-income economies and only gradual withdrawal of the monetary and fiscal stimulus across the region. We project real GDP growth will settle to about 8 percent in 2011 and 2012 from about 9.6 percent in 2010. Inflation has become the key short-run challenge for the authorities in the region, complicated by a surge in portfolio capital inflows and rapidly increasing food and commodity prices that hit low-income households disproportionately. For many middle-income countries in East Asia, lowering inflation presents difficult policy choices. Most have eschewed the use of capital controls, and allowing exchange rates to appreciate may protect against importing inflation but jeopardizes international competitiveness. The sharp increase in commodity prices portends increased volatility for the foreseeable future. All commodity prices are on an upswing, some either at all-time highs or at levels exceeding those reached only two years ago. These latest price developments continue the trend that began earlier this decade of a steady climb in real commodity prices, interrupting a decade-long downward trend in the 1990s. Policies to provide incentives and ensure the investment needed to help develop new and greener energy sources, notably with low-carbon emissions and much improved energy efficiency should be a priority for governments in the region. Output growth throughout developing East Asia moderated in the second half of 2010 but was still surprisingly strong. This positive outcome reflected sustained monetary and fiscal stimulus measures and stronger growth in demand abroad, both of which partly offset the return of capacity utilization to pre-crisis levels. Real GDP growth in developing East Asia and Pacific amounted to 9.6 percent for 2010 as a whole 0.7 percentage points higher than our estimate in November 2010.